A Crude Depiction of Oil: A Comparative Discourse Analysis of CBC Calgary and British Columbia's Coverage of the Trans Mountain Pipeline Expansion Project - Abounehme, Kayla (Université d'Ottawa | University of Ottawa, 2020)
As fossil fuels become increasingly associated with images of ecological destruction and humanitarian concerns, many have come to question the future viability of Alberta’s oil sands. In the face of uncertainty, the fossil fuel industry and Alberta government attempt to secure public consent for resource extraction by legitimizing the assumption that fossil fuel development as imperative to economic and social welfare. Accordingly, this research paper will examine the news media’s role in facilitating this process by sponsoring hegemonic neoliberal discourses touting the promise of oil sands, while silencing dissenting voices highlighting its environmental and social repercussions. While the majority of literature focuses on the mainstream media, scant research has examined the role of public service broadcasting (PSB) in this matter, despite the crucial role they play in sustaining democracy. Consequently, this research fills this gap in the literature by analyzing the Canadian Broadcasting Corporation’s (CBC) framing of the controversial Trans Mountain Pipeline expansion project (TMX) in a bid to examine whether it’s fulfilling its mandate to remain unfettered by corporate and government influences. Specifically, it involves a Critical Discourse Analysis (CDA) of CBC Calgary (N=12) and CBC British Columbia (N=15) to gauge whether local attitudes, values, and beliefs towards the fossil fuel industry are reflected in their respective framing of TMX. Overall, the findings reveal that while CBC B.C. and Calgary’s coverage does reflect local attitudes surrounding TMX, the CBC Calgary’s narratives reflect the neoliberal discourses sponsored by the Alberta government and fossil fuel industry, thus raising questions about the relationship between public broadcasting, democratic institutions, and the corporate interests of the fossil fuel industry.